MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI METODE COOPERATIVE LEARNING DALAM PEMBELAJARAN PAI - Nurotun Mumtahanah (Al Hikmah: Jurnal Studi Keislaman, 2013)
One of the competencies required by a professional teacher is the ability to organize learning materials. To perform these tasks, teachers should have the skills of how to plan lessons according to the characteristics of the material as well as the characteristics of student learning, the school environment and surrounding communities. Then the search effort and application of appropriate learning models in order to enforce higher quality teaching and learning process. One of the methods that can create critical thinking skills of students in the learning PAI is a method of cooperative learning. Critical thinking is not the same as being critical. Be critical if inclined to express our response directly through a real attitude and action, without first considering/thinking about whether or not the response to the information that we get. While critical thinking is a mindset to look at a solution of the problems occurred. It is worth learning (cooperative learning) is an alternative model of innovative learning and can improve the quality of learning PAI, which in general can improve the quality of national education